VALUE ADDED TAX – VAT A CENTENARIAN [1920-2020] IN THIS COVID-19 - Narayanan, Hariharan (International Journal of Research -GRANTHAALAYAH, 2020)
Value Added Tax is an indirect tax which is also termed as Goods and Service Tax. Both these terms are used in the same meaning in different parts of the world. VAT is followed almost in many countries and during this pandemic situation many countries have relaxed VAT for the benefit of the public. This study mainly focuses on the frameworks followed by various nations regarding VAT. It concentrates on the origin, growth and development of VAT, various tax model frameworks followed in nearly 147 different countries all around and the various measures adopted by countries towards VAT during this era of COVID-19 pandemic.